Predictors of Clinically Significant Echocardiography Findings in Older Adults with Syncope: A Secondary Analysis. Issue 12 (26th September 2018) - Probst, Marc A.; Gibson, Thomas A.; Weiss, Robert E.; Yagapen, Annick N.; Malveau, Susan E.; Adler, David H.; Bastani, Aveh; Baugh, Christopher W.; Caterino, Jeffrey M.; Clark, Carol L.; Diercks, Deborah B.; Hollander, Judd E.; et al.
Abstract : BACKGROUND: Syncope is a common reason for visiting the emergency department (ED) and is associated with significant healthcare resource utilization. OBJECTIVE: To develop a risk‐stratification tool for clinically significant findings on echocardiography among older adults presenting to the ED with syncope or nearsyncope. DESIGN: Prospective, observational cohort study from April 2013 to September 2016 SETTING: Eleven EDs in the United States PATIENTS: We enrolled adults (≥60 years) who presented to the ED with syncope or near‐syncope who underwent transthoracic echocardiography (TTE). MEASUREMENTS: The primary outcome was a clinically significant finding on TTE. Clinical, electrocardiogram, and laboratory variables were also collected. Multivariable logistic regression analysis was used to identify predictors of significant findings on echocardiography. RESULTS: A total of 3, 686 patients were enrolled. Of these, 995 (27%) received echocardiography, and 215 (22%) had a significant finding on echocardiography. Regression analysis identified five predictors of significant findings: (1) history of congestive heart failure, (2) history of coronary artery disease, (3) abnormal electrocardiogram, (4) high‐sensitivity troponin‐T >14 pg/mL, and 5) N‐terminal pro B‐type natriuretic peptide >125 pg/mL. These five variables make up the ROMEO (Risk Of Major Echocardiography findings in Older adults with syncope) criteria. The sensitivity of a ROMEO score of zero for excluding significant findings on echocardiography was 99.5% (95% CI: 97.4%‐99.9%) with a specificity of 15.4% (95% CI: 13.0%‐18.1%). CONCLUSIONS: If validated, this risk‐stratification tool could help clinicians determine which syncope patients are at very low risk of having clinically significant findings on echocardiography. FUNDING: This project was supported by the National Heart, Lung, and Blood Institute of the National Institutes of Health under Award Number R01 HL111033. Dr. Probst is supported by the National Heart, Lung, and Blood Institute of the National Institutes of Health under Award Number K23HL132052‐02.